ACC deaminase-producing bacteria mitigate water deficit in tomato seeds - Helena Souza Nascimento Santos; Regina Cássia Ferreira Ribeiro; Andréia Márcia de Souza David; José Augusto dos Santos Neto; Adelica Aparecida Xavier; João Rafael Prudêncio Santos (Journal of Seed Science)
ABSTRACT: Bacteria that modulate ethylene levels through the enzyme 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase are a promising strategy to mitigate the effects of water stress. The aim of this study was to assess the effect of these bacteria on the germination and growth of tomato seedlings subjected to water deficit. The experiment was conducted using a completely randomized design and 6x5 factorial scheme, with six seed treatments (four bacterial isolates and two controls) and five PEG 6000-induced osmotic potentials (0.0, -0.2, -0.4, -0.6, and -0.8 MPa), with four replications of 50 seeds. Germination, radicle protrusion, first germination count (FGC), germination speed index (GSI), and the fresh weight, root and shoot length of seedlings were evaluated. The results indicated that bacteria with ACC-deaminase activity favored germination and seedling development under water stress. Although water deficit reduced germination, isolate RZ-1 effectively mitigated these effects at -0.4 MPa. Strains E-154 and E-24 promoted the highest root and shoot growth.